Seizure: An Etruscan Hare Alabastron, circa 580-560 B.C.E. Reprinted from ARCA Blog, Friday, June 29, 2018. (Les Carnets de l’ACoSt)
An ancient Etruscan terracotta vessel in the shape of a reclined rabbit.  Listed as a Hare Aryballos (sic), circa 580-560 B.C.E., the unguentarium was seized by New York authorities at Fortuna Fine Arts Ltd. Reprinted from the ARCA Blog, Friday, June 29, 2018.